Social networks and wages: It is all about connections! - Mauro Sylos Labini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2005)
Empirical evidence suggests that networks of personal relations are important in the micro dynamics of labor markets: even in modern capitalistic economies a high share of jobs are filled by social referrals. This paper aims at shedding light on an apparent puzzle concerning the relationship between the use of informal contacts and wages. First, the paper argues that economic perspectives concerning such relationship might benefit from considering important differences in the nature of social ties. Second, a formal model which considers two distinct informal contacts dubbed family and professional is proposed. The model predicts that while the use of the former type is likely to have a negative impact on wages, the opposite is true for the latter. Third, a relatively unexploited Italian data set is used to show that distinct ties have different properties and are likely to be used by different individuals. Finally, the paper concentrates on the relation between informal contacts and wages, obtaining results consistent with the foregoing theoretical insights.
Keywords: A14; J31; J41; Z13; 330; Labor Markets; Job Search; Social Networks; Arbeitsmarkt; Arbeitsuche; Italien; Soziales Netzwerk